(untitled) - FAO (Rome, 1996)
In its capacity as the International Commodity Body for fishery products, the Sub-Committee noted the progress achieved in its cooperation with the Common Fund for Commodities and in this respect requested the Secretariat to draft a document which would address the technical aspects of a Strategy for the Development of Fishery Commodities.
Keywords: fisheries